Civil War and Citizens' Demand for the State: An Empirical Test of Hobbesian Theory. Issue 4 (8th October 2022) - Blair, Robert A.
Abstract: How does violence during civil war shape citizens' demand for state-provided security, especially in settings where non-state actors compete with the state for citizens' loyalties? This article draws on Hobbesian theory to argue that in post-conflict countries, citizens who were more severely victimized by wartime violence should substitute away from localized authorities and towards centralized ones, especially the state. The author tests the theory by combining two original surveys with existing media and non-governmental organization data on wartime violence in Liberia. The study shows that citizens who were more severely affected by violence during the Liberian civil war are more likely to demand state-provided security, both in absolute terms and relative to non-state alternatives. More sporadic collective violence in the post-conflict period does not reverse this substitution effect. Also consistent with Hobbesian theory, citizens who were more severely victimized are more fearful of threats to peace almost a decade later.